Numerical Study of Shell-And-Tube Heat Exchanger Characteristicsin Laminar Flow with Single Segmental Baffle - Novan Ardhiyangga; Teguh Hady Ariwibowo; Prima Dewi Permatasari (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Shell-and-tube heat exchangers (STHEs) are one of the most popular heat exchanger due its flexibility to allow wide range pressure and temperature. The shell-sideperforms very complex flow which result in the difficult of analysis. This paper examines the characteristic of shell-side which obtained by adjusting vary of mass flow rates to gain laminar flow condition. A certain STHE with single segmental baffle used in this analysis that run by the stream analysis method developed by Heat Transfer Research Inc. (HTRI). The result shows that the increase value of mass flow rate will increase the shell-side heat transfer coefficient, pressure drop, and heat exchanger effectiveness. The increase value of mass flow rate from 0.1065 kg/s to 0.1775 kg/s will increase the shell-side heat transfer coefficient about 37.56% where minimum and maximum values are 1557.58 and 2142.76 W/m2.K. The shell-side pressure drop also increase from 0.325 kPa to 0.898 kPa or up to 176.31% increase. The heat exchanger effectiveness increase with the lower number of 7.02% from 0.276 to 0.295. From this experiment, it can be inferred that the increase value of mass flow rate in shell-side will be good to the heat exchanger performance, but the increase value of pressure drop must be in consideration too.